The Consequences of Sago Planting Hamlet Program on Socio-Cultural Changes of The Kamoro in Mimika Papua - Rudy G. Erwinsyah (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2022)
This study examines the consequences of various agrarian policies and development programs on the Kamoro community in Mimika Regency, Papua Province. As a result of FI Mining activities, the Kamoro people, who were originally nomads on their customary lands, were relocated to permanent settlement where they were introduced to intensive farming systems, one of which was the Sago Planting Hamlet (SPH/DST) Program that brought modern sago farming management. There was a contradiction because the Kamoro people have been accustomed to rice as their staple for decades due to the national food policy during the New Order era and the damage to their ecological environment, especially wild sago forests. This study tries to see how the socio-cultural consequences in the community since the implementation of intensive agricultural programs are relatively new to them. Research question were answered through a descriptive qualitative approach, with primary data from in-depth interviews and participatory observations, supported by secondary data from the archive and document searches, also spatial data from Landsat imagery. The results showed that the implementation of the DST Program brought the consequences of socio-cultural changes to the Kamoro people, which included adjustments to social organization, livelihoods, and natural resource management. What happened to the Kamoro: the collapse of the production, reproduction, and consumption systems of society due to the alienation of traditional living cultures that rely on the availability of natural sources of livelihood, has made the Kamoro undeveloped. Keywords: Intensive agriculture, Kamoro, sago plantations, socio-cultural changes